Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to solve this question:

Let $f:(c,+\infty)\to \mathbb R$ be differentiable. If the limits $\lim_{x\to+\infty}f(x)=a$ and $\lim_{x\to+\infty}f'(x)=b$ exist with $a\in \mathbb R$, then $b=0$.

There is a hint, it says $f(n+1)-f(n)=f'(x_n)$, where $x_n\to \infty$

I didn't understand this hint.

I need help, any clue is welcome.

Thanks a lot

share|cite|improve this question
The question title seems to make a stronger claim than the one in the question body (and the stronger claim is wrong.) – Trevor Wilson Feb 7 '13 at 1:46
Counterexample showing that the condition $\lim_{x\to\infty}f'(x) = b$ is necessary: $f(x) = \frac{1}{x}\sin(x^2)$. – Ayman Hourieh Feb 7 '13 at 9:29
up vote 6 down vote accepted

Apply the mean value theorem to $[n, n+1]$ to find $x_n \in (n, n+1)$ so that: $$ f'(x_n) = \frac{f(n+1) - f(n)}{(n+1) - n} = f(n+1) - f(n) $$

Now evaluate: $$ \lim_{n\to\infty} f'(x_n) = \lim_{n\to\infty}\left(f(n+1) - f(n)\right) $$

Since $\lim_{x\to\infty} f'(x)$ exists, what do you conclude?

share|cite|improve this answer
then we have $\lim_{n\to\infty}f'(x_n)=\lim_{n\to\infty}\left(f(n+1) - f(n)\right)= a-a=0$? – user42912 Feb 7 '13 at 1:58
@user42912 Yes! – Ayman Hourieh Feb 7 '13 at 2:14
thank you very much for your answer! – user42912 Feb 7 '13 at 3:13
Nice answer (+1). – Mhenni Benghorbal Feb 7 '13 at 7:05

Just to understand this result intuitively, suppose $b>0$. Then $b>b/2>0$ and so from some point onwards on the $X$ axis the derivative satisfies $f'(x)>b/2$ and so from that point onwards the function $f$ is increasing at a rate of no less then $b/2>0$. Clearly such a function will thus tend to $\infty $ and not to a finite $a$ as given. The case $b<0$ is treated similarly.

The hint suggested a very clear solution as the other answers show. For diversity, and since I like formal solutions that follow an intuitively clear informal argument, here is a solution along the lines in the preceding paragraph.

Assume to the contrary that $b\ne 0$. It will suffice to consider the case $b>0$ as the case $b<0$ will follow by considering the function $g(x)=-f(x)$. Since $\lim _{x\to \infty }f'(x)=b$ there exists $x_0$ such that for all $x>x_0$ holds that $f'(x)>b/2$ (take $\epsilon = b/2$ in the definition of limit). Consider any $y>x_0$ and apply the Mean Value Theorem on $[x_0,y]$ to obtain some $x_0<t<y$ such that $f'(t)=(f(y)-f(x_0))/(y-x_0))$. Rearrange to get $f(y)=f'(t)(y-x_0)+f(x_0)$. Recalling that $f'(t)>b/2$ we obtain $f(y)>y-x_0+f(x_0)$. As $x_0$ is fixed it follows that $\lim _{y\to \infty }f(y)=\infty $, a contradiction.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.